Toward user-defined element types and architectural styles - DeLIne, Robert (ISAW '96 Joint proceedings of the second international software architecture workshop, 1996)
When considering the design of an architectural description language (ADL) to be used as part of a software developer's daily practice, two goals merit attention. First, the language should support the easy definition of new element types and architectural styles. Second, it should play a central role in system construction. A proposed adl, called UniCon-2, addresses these goals with its flexible type system, its duty construct, and its extensible compiler architecture based on ole. Such an adl provides a good starting point for exploring the architectural description of families of systems and flexible componentry.